TATA KELOLA OPTIMAL WAKTU KERJA PADA USAHA KECIL GALON DENGAN METODE HUNGARIAN : STUDI KASUS DI GALON IBU WASTY - Rumetna, Matheus Supriyanto; Ninia Lina, Tirsa; Delima, Fansya; Laisoka, Chrestian; Janri Paembonan, Gabriel; Aifufu, Amos; Dewi, Sandra; Omkharsba, Wehelmina (Journal of Computer Science and Technology (JCS-TECH), 2024)
This research discusses the optimal management of working time at Ibu Wasty's Galon Business using the Hungarian Method. Ibu Wasty's Galon Business, which was founded on December 23 2022 and is located at Malibela Street km 10.5 Kasrem Housing, is a small business initiative that aims to meet the community's need for clean water in gallon containers. Its strategic location makes this business the main choice for local residents to obtain their daily drinking water needs easily and efficiently. This case study focuses on how applying the Hungarian Method can optimize resource allocation and employee work time to increase operational efficiency. Ibu Wasty's Galon business faces challenges in dividing work time, which is important to maintain smooth operations and service quality. By utilizing the POM-QM application, this research shows that the Hungarian Method can be applied effectively to develop optimal work schedules. The research results show increased operational efficiency and more systematic and accurate working time management, with a total optimal working time of 6 hours. It is hoped that these findings will contribute to the operational management literature and provide practical guidance for small businesses in managing employee working time